IMPAIRED DARK ADAPTATION ASSOCIATED WITH A DISEASED BRUCH MEMBRANE IN PSEUDOXANTHOMA ELASTICUM. Issue 10 (October 2020) - Hess, Kristina; Gliem, Martin; Birtel, Johannes; Müller, Philipp; Hendig, Doris; Andrews, Colm; Murray, Ian J.; Holz, Frank G.; Charbel Issa, Peter
Abstract : Purpose: To characterize dark adaptation in patients with pseudoxanthoma elasticum, a systemic disease leading to calcification of elastic tissue including the Bruch membrane. Methods: In this prospective case–control study, dark adaptation thresholds were measured using a Goldmann-Weekers dark adaptometer. Additional assessments included best-corrected visual acuity testing, contrast sensitivity, low luminance deficit, and vision-related quality of life. Results: Dark adaptation thresholds were significantly higher, and adaptation periods were prolonged in patients with pseudoxanthoma elasticum (n = 35; 33 with 2 ABCC6 mutations) compared with controls (n = 35). The time to adapt 4 log units (20.6 ± 8.6 vs. 8.0 ± 1.3 minutes) and the mean dark adaptation threshold after 15 minutes (3.5 ± 1.1 vs. 1.8 ± 0.2 log units) were significantly different between patients and controls (both P < 0.001). Low luminance deficits (12.3 ± 6.4 vs. 6.1 ± 4.3 ETDRS letters), contrast sensitivity (1.4 ± 0.3 vs. 1.9 ± 0.1), and low luminance-related quality of life (LLQ score: 1, 286 ± 355 vs. 2, 167 ± 68) were also significantly worse in patients with pseudoxanthoma elasticum (all, P < 0.001). Two patients were treated with high-dose vitamin A which partially reversed impaired dark adaptation. Conclusion: Patients with pseudoxanthoma elasticum often have impaired dark adaptation. Positive effects of vitamin A supplementation may indicate restricted retinal access of vitamin A through the Bruch membrane as one possible underlying pathogenic factor. Abstract : Dark adaptation is significantly impaired in patients with pseudoxanthoma elasticum and may be partially reversed by supplementation of high doses of vitamin A.